Measurements with silicon photomultipliers of dose-rate effects in the radiation damage of plastic scintillator tiles in the CMS hadron endcap calorimeter; Journal of Instrumentation; Vol. 15, iss. 6 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen